Determination of the electronic configuration of the ground state of iron dimer through analysis of fe57m mössbauer data - Mishra, Kailash C.; Duff, Kenneth J.; Kelires, Pantelis C. (My University, 1986)
The hyperfine properties of Fe57m in the diatomic iron molecule have been analyzed using the self-consistent-field unrestricted Hartree-Fock procedure. The Fe57m quadrupole interaction and isomer shift strongly support g3 as the ground state for the Fe2 molecule, with g7 leading to less satisfactory agreement with experimental data but better than for other possible states. The analysis of the magnetic hyperfine-field tensor also appears to provide support for the g3 model through agreement with the evidence from Mössbauer studies that the direction of the maximum component is perpendicular to the internuclear axis, the direction of the maximum component of the electric-field-gradient tensor. The magnitudes of the hyperfine-field components are however underestimated by a factor of about 2 compared to experiment. Possible sources that could contribute to this departure are discussed.
Keywords: Electronics; Iron; Diatomic molecules